M1 macrophages – unexpected contribution to tumor progression - Olga V. Kovaleva; Madina A. Rashidova; Vasiliy V. Sinyov; Olga S. Malashenko; Alexei Gratchev; Alexei Gratchev (Frontiers in Immunology)
The anti-tumor role of the immune system has long been associated with interferon-γ-mediated activation of immune cells and their ability to recognize and eliminate transformed cells. Fundamental principles of tumor immunoediting describe a dynamic interplay between the immune system and neoplastic cells, wherein immune pressure can paradoxically shape tumor evolution. Within this context, macrophages, natural killer cells, and T lymphocytes are central effectors of anti-tumor immunity. Traditionally, macrophages exhibiting M1 phenotype are characterized by high cytotoxic potential and considered important contributors to tumor eradication. In contrast, M2-polarized tumor-associated macrophages are associated with immune suppression and tumor progression. However, recent evidence challenges this binary paradigm. It is increasingly evident that M1 macrophages, while initially exerting anti-tumor effects, can also promote tumor progression by applying sustained cytotoxic pressure that selects for more malignant and immune-resistant tumor clones. This phenomenon represents an unexpected and overlooked contribution of cytotoxic macrophages to tumor progression. In this review, we examine the complex, context-dependent function of M1 macrophages and reassess current strategies aimed at enhancing their cytotoxicity. While such approaches may offer short-term benefits, they risk driving clonal selection of aggressive, immune-evasive tumor cells. Therefore, we propose a paradigm shift: instead of promoting M1 polarization alone, therapeutic strategies should consider the broader consequences of macrophage–tumor interactions. A nuanced understanding of macrophage plasticity and tumor dynamics is essential for designing effective immunotherapies. Recognizing the paradoxical role of M1 macrophages is critical to avoiding unintended support of tumor evolution and improving treatment outcomes.